Getting the Bias Wrong: Educational Opportunities for Boys and Girls in Mexico - Aguayo-Téllez, Ernesto; Chapa-Cantú, Joana; Rangel-González, Erick; Treviño-Villarreal, Lourdes (Journal of Research in Educational Sciences, 2012)
The First National Survey on Discrimination in Mexico, conducted in 2004, reported that 15 out of every 100 parents think they should not invest in their daughter´s education because they will ultimately get married and it will be a waste of money. Using data from the Mexican Income-Expenditure Survey waves of 1992, 1998 and 2004, we did not find enough statistical evidence to support the idea that families provide less education to their 15 to 18 years old daughters. In fact, contrary to common belief, our results suggest the existence of a small pro-girl discrimination in education access at secondary school.